The Muslim Brotherhood, Its Youth, and Implications for U.S. Engagement - Martini, Jeffrey (RAND Corporation, 2012)
Since the 2011 revolution in Egypt, the Muslim Brotherhood has emerged as a key political player. Although individuals under the age of 35 make up a large share of the membership, the group's strict hierarchy has led to disaffection among its youth. These members merit attention not only as a challenge to the Brotherhood's organizational cohesion, but as a potential conduit for expanding U.S. engagement with the group.